2015
DOI: 10.1039/c4ta01304b
|View full text |Cite
|
Sign up to set email alerts
|

Site specific supramolecular heterogeneous catalysis by optically patterned soft oxometalate–porous organic framework (SOM–POF) hybrid on a chip

Abstract: We have designed a supramolecularly bound multi-component catalytic material based on a soft oxometalate (SOM) and a porous organic framework (POF) material, which shows high catalytic conversion efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 61 publications
0
52
0
Order By: Relevance
“…It has been shown by us and others that each of the components of the above host-guest species [PMo 12 @Mo 72 Fe 30 ] i.e., PMo 12 and Mo 72 Fe 30 independently shows superstructured soft-oxometalate (SOM) formation by spontaneous assembly in colloidal lengthscales. 1,2,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] We have previously shown that a dilute sonicated dispersion of PMo 12 leads to the formation of peapod 37 like SOM structures. Initially, the peapods have nanosphere-type morphology and with time these spheres get converted to nanorods with nanospheres embedded inside this rod.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown by us and others that each of the components of the above host-guest species [PMo 12 @Mo 72 Fe 30 ] i.e., PMo 12 and Mo 72 Fe 30 independently shows superstructured soft-oxometalate (SOM) formation by spontaneous assembly in colloidal lengthscales. 1,2,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] We have previously shown that a dilute sonicated dispersion of PMo 12 leads to the formation of peapod 37 like SOM structures. Initially, the peapods have nanosphere-type morphology and with time these spheres get converted to nanorods with nanospheres embedded inside this rod.…”
Section: Introductionmentioning
confidence: 99%
“…POMs are generally ionic in nature with high charge and a number of hydrogen bonding sites, which provides the possibility to synthesize composites with different electro active surfaces such as graphene, graphene oxide, different LDHs ,. The immobilization of the POM moiety on the electro active surface can enhance the catalytic activity of these materials ,. POMs can also exist in a colloidal state of soft‐oxometalates (SOMs) .…”
Section: Introductionmentioning
confidence: 99%
“…This aggregate can be recovered and self‐organized again into a new SOM shell of a desired size and the cycle of polymerization continues. Moreover, to the best of our knowledge, such a method of surfactant‐free and initiator‐free controlled polymerization is not known in the literature to date . In the next section we review the literature briefly to explain the design of our system.…”
Section: Introductionmentioning
confidence: 99%